2017
DOI: 10.1098/rsta.2017.0045
|View full text |Cite
|
Sign up to set email alerts
|

Structure of native cellulose microfibrils, the starting point for nanocellulose manufacture

Abstract: There is an emerging consensus that higher plants synthesize cellulose microfibrils that initially comprise 18 chains. However, the mean number of chains per microfibril is usually greater than 18, sometimes much greater. Microfibrils from woody tissues of conifers, grasses and dicotyledonous plants, and from organs like cotton hairs, all differ in detailed structure and mean diameter. Diameters increase further when aggregated microfibrils are isolated. Because surface chains differ, the tensile properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
96
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 74 publications
4
96
0
1
Order By: Relevance
“…According to the current understanding (Jarvis 2018), however, such extensive amorphous domains do not exist in the CMFs of native wood cell walls, even though disordered regions of a few glucose units with a much longer periodicity (150 nm) have been reported for ramie fibers (Nishiyama et al 2003). Therefore, alternative explanations for the finite correlation length in the longitudinal direction of CMFs have been suggested, a chiral twist around the longitudinal axis and bending of the longitudinal axis probably being the strongest candidates (Fernandes et al 2011;Jarvis 2018). Bending or buckling of CMFs has been proposed to take place during drying of the G-layer in tension wood (Clair et al 2006) and it is possible that similar but weaker changes occur also in the lignified cell walls of normal woods.…”
Section: :2åmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the current understanding (Jarvis 2018), however, such extensive amorphous domains do not exist in the CMFs of native wood cell walls, even though disordered regions of a few glucose units with a much longer periodicity (150 nm) have been reported for ramie fibers (Nishiyama et al 2003). Therefore, alternative explanations for the finite correlation length in the longitudinal direction of CMFs have been suggested, a chiral twist around the longitudinal axis and bending of the longitudinal axis probably being the strongest candidates (Fernandes et al 2011;Jarvis 2018). Bending or buckling of CMFs has been proposed to take place during drying of the G-layer in tension wood (Clair et al 2006) and it is possible that similar but weaker changes occur also in the lignified cell walls of normal woods.…”
Section: :2åmentioning
confidence: 99%
“…1) is bound to hydroxyl groups of hemicelluloses and the surfaces of cellulose microfibrils (CMF) (Engelund et al 2013). The 2 to 3-nm-thick CMFs, together with hemicelluloses, are aggregated into bundles, which swell by the adsorption of water (Jarvis 2018). Lignin is also included in the secondary cell wall, where it is closely associated with hemicelluloses and possibly also cellulose, providing a more robust and less watersensitive matrix for the CMFs (Kang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As for secondary cell wall AtCESAs , AtCESA1 and AtCESA3 are non‐redundant, whereas AtCESA6 is partially redundant with AtCESA2 and AtCESA5 (Desprez et al ., ; Persson et al ., ). Evidence that rosette CSCs contain 18 subunits (Nixon et al ., ; Jarvis, ) and that the CESA isoform stoichiometry is 1:1:1 for both primary and secondary cell wall CSCs in Arabidopsis (Gonneau et al ., ; Hill et al ., ) supports a ‘hexamer of trimers’ model in which three CESA isoforms occupy distinct positions within each lobe of their respective CSCs (Hill et al ., ; Nixon et al ., ; Jarvis, ). Phylogenetic analysis of CESA families has shown that all seed plants analyzed contain CESA sequences that cluster with members of each of the Arabidopsis primary and secondary CESA classes (Kumar et al ., ; Carroll and Specht, ; Jokipii‐Lukkari et al ., ), indicating that hetero‐oligomeric rosette CSCs with a hexamer of trimers organization evolved before the divergence of gymnosperms and angiosperms.…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of the molecular architecture and ultrastructure of cell walls is needed to describe the complex spatiotemporal deposition pattern of the cell wall polymers. This may contribute to the development of more efficient biofuel feedstocks (Loque et al, 2015), to the improvement in our understanding of novel biomaterials such as nanocellulose (Jarvis, 2018), and to applications such as advanced approaches for the use of timber in the construction industry (Ramage et al, 2017)…”
Section: Introductionmentioning
confidence: 99%